Interactive Effects on Motor Performance of Mindfulness, Performance Under Pressure, Self-Talk, and Motor Task Characteristics. Issue 2 (April 2022) - Liu, Hong-Yu; Lu, Frank J. H.; Hsu, Yawen; Gill, Diane L; Chiu, Yi-Hsiang; Peng, Yu-Hao
High mindfulness individuals have been found to perform better on motor tasks under various conditions, but it is unknown whether mindfulness and performance relate when performing under pressure or using different types of self-talk with different motor tasks. In this study, 46 male participants ( M age = 21.4, SD = 1.72 years) with high mindfulness ( n = 23) and low mindfulness ( n = 23) performed dart-throwing and two-hand coordination tasks under pressure and non-pressure conditions and when using instructional and unrelated self-talk. First, on the two-hand coordination task, a three-way mixed ANOVA found: (a) a significant 3-way interaction in which a significantly poorer performance occurred under pressure (vs. without pressure), with low (vs. high) mindfulness and when using unrelated (vs. instructional) self-talk and (b) a significant interaction in which, both under pressure and not, both high and low mindfulness participants performed comparably when using instructional (vs. unrelated) self-talk. Second, on the dart-throwing task, mindfulness interacted with self-talk such that both high and low mindfulness participants performed better when using instructional self-talk, and pressure interacted with self-talk such that participants using instructional (vs. unrelated) self-talk performed better in both pressure and non-pressure conditions. We concluded that instructional self-talk was a useful cognitive strategy, perhaps particularly in pressure conditions and regardless of the degree of mindfulness, and its effectiveness extended to two different motor tasks. We discussed the theoretical implications of these findings, in terms of attention theory, self-talk, and motor control; and we highlighted our study's limitations and practical applications and gave recommendations for future research.